2023
DOI: 10.1136/bmjmed-2022-000318
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive outcomes in women and men conceived by assisted reproductive technologies in Norway: prospective registry based study

Abstract: ObjectivesTo determine whether the perinatal outcomes of women or men who were conceived by assisted reproductive technologies are different compared with their peers who were naturally conceived.DesignProspective registry based study.SettingMedical Birth Registry of Norway.ParticipantsPeople born in Norway between 1984 and 2002 with a registered pregnancy by the end of 2021.ExposurePeople who were conceived by assisted reproductive technologies and have had a registered pregnancy.Main outcome measuresComparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Research has found little evidence that people conceived as a result of fertility treatment have a greater risk of pregnancy complications or worse birth outcomes than their naturally conceived peers when becoming parents, a study in BMJ Medicine reported 3. While IVF conception is associated with fewer pregnancies in adulthood, this may well be explained by social rather than clinical factors, the researchers said.…”
Section: Pregnancymentioning
confidence: 99%
“…Research has found little evidence that people conceived as a result of fertility treatment have a greater risk of pregnancy complications or worse birth outcomes than their naturally conceived peers when becoming parents, a study in BMJ Medicine reported 3. While IVF conception is associated with fewer pregnancies in adulthood, this may well be explained by social rather than clinical factors, the researchers said.…”
Section: Pregnancymentioning
confidence: 99%
“…Assisted reproduction technologies (ART) include any treatments related to fertility in which eggs or embryos are manipulated to attain a pregnancy, including in-vitro fertilisation and intracytoplasmic sperm injection. 1 The first baby born by in-vitro fertilisation was in 1978, which was the starting point of ART worldwide. More than 10 million children have since been born in the past 40 years.…”
mentioning
confidence: 99%
“…To address this gap, Carlsen and colleagues in the linked article by BMJ Medicine report the findings of the first study to examine this association. 1 Carlsen and colleagues analysed data from the Norwegian Medical Birth Registry and included all women and men born in Norway from 1984 (which was the year of the first baby born who was conceived by ART in Norway) to 2002, which accounted for just more than one million people. The authors then followed up this population up to 2021 and identified all registered pregnancies linked to these women and men.…”
mentioning
confidence: 99%
See 2 more Smart Citations